Thyroid hormonal inducing drugs and their impact on neurological diseases: An integrative literature review (Research, Society and Development, 2024)
Objective: To conduct an integrative literature review on the effects and mechanisms of action of thyroid hormone-inducing drugs in the treatment of neurological diseases. Method: An integrative literature review was used including the definition of the theme, inclusion and exclusion criteria, evaluation, and interpretation of studies. The search was conducted in various databases such as Scopus, PubMed, CINAHL, Web of Science, LILACS, BDENF, and SciELO. Results: Out of the 954 studies initially identified, 10 were included in the final analysis after a rigorous screening and quality assessment process. The key categories identified were “Thyroid Hormone-Inducing Drugs,” “Target Neurological Diseases,” “Therapeutic Effects,” and “Pharmacological Considerations.” These categories range from the study of specific drugs and their physiological interactions to the therapeutic impacts and practical considerations in administering these drugs. Conclusions: It is concluded that this work consolidates current knowledge and opens new perspectives at the intersection of endocrinology with neurology, aiming for continuous improvement in the quality of life of patients with complex neurological conditions.